ATIM-12. AVELUMAB IN NEWLY DIAGNOSED GLIOBLASTOMA MULTIFORME-THE SEJ STUDY. (11th November 2019) - Jacques, Francois; Nicholas, Garth; Lorimer, Ian; Sikatifoko, Victorine; Dumais, Nathalie
Abstract: INTRODUCTION: Glioblastoma Multiforme (GBM) has well documented systemic and local immunosuppressive mechanisms to escape immune surveillance. GBM tumor cells as well as the microglia within it have a high PD-L1 surface expression which may make it susceptible to anti-PD-L1 antagonism and ADCC with avelumab therapy. Combining immunotherapy to other chemotherapeutic agents have proven benefical in certain cancers. A clinical trial looking at adding avelumab to standard therapy in patients with newly diagnosed GBM is indicated. METHODS: This is a single center, phase 2, open label study of avelumab 10 mg/kg Q2W for 156 weeks duration in patients receiving standard therapy for newly diagnosed GBM. Thirty patients will be entered into the study within 3 weeks of completing combined radiotherapy/temozolomide. Here we will report the results our second interim analysis when the first 20 patients will have completed 52 weeks or an end of study event which will occur in 10–2019. RESULTS: The results will be presented at the meeting